Comparison of mediating factors associated with cognitive function between normal weight and overweight/ obese children in Kuala Lumpur, Malaysia - Tung, Serene En Hui (2017)
Recent research suggests that a negative relationship exist between adiposity and cognitive function in children. However, limited information is known on how they were related. The negative relationship between overweight/obesity with cognitive performance may be related both directly and indirectly via obesity-related behaviours, psychological well-being and cardiovascular disease risk factors. Hence, this study aimed to compare the mediating factors associated with cognitive function in normal weight and overweight/obese children aged 10-11 years in Kuala Lumpur, Malaysia. This cross-sectional comparison study was conducted in twelve primary schools selected using multi-stage stratified random sampling method. A total of 1971 children were screened for BMI-for-age through measurement of height and weight. A total of 235 overweight/obese children were selected and matched for age, sex, and ethnicity with 226 normal weight children. Anthropometric measurements included weight, height, waist circumference (WC) and body fat percentage (BF%). Dietary intake and physical activity were assessed using a two-day 24 hour dietary intake and physical activity recall. A self-administered questionnaire was used to gather information on socio-demographic factors and assessed self-esteem, body image, disordered eating and depression. Blood pressure was measured and venous blood was drawn after an overnight fast to determine insulin, high-sensitivity C-reactive protein (hs-CRP), glucose and lipid profiles. Homeostasis model assessment-estimated insulin resistance (HOMA-IR) was calculated using glucose and insulin levels. Cognitive function such as perceptual reasoning, verbal comprehension, working memory and processing speed were measured by using Wechsler’s Intelligence Scale for Children (WISC-IV). Out of the 1971 children who were screened for BMI-for-age, 32.3% were found to be overweight/obese. Overweight/obese children had significantly higher energy intake (t=- 2.395; p=0.017), lower energy expenditure (t=-3.512; p<0.001), higher body image discrepancy scores (t=5.390; p<0.001) and disordered eating scores (t=-3.512; p<0.001) and poorer biochemical parameters (p<0.05) compared to their normal weight counterparts. Ordinary Least Square (OLS) regression analysis was conducted to determine the direct and indirect relationships between weight status with cognitive function. Negative relationships were found between overweight/obesity with perceptual reasoning, verbal comprehension, working memory, processing speed and cognitive function scores (Full IQ scores). Overweight/obese children were on average 4.075 units lower in their cognitive function scores (Full IQ scores) compared to their normal weight counterparts. Such difference was found as a result of the mediators body image (β=-0.482; 95% CI [-1.374, -0.041], disordered eating (β= -1.021; 95% CI [-2.081, -0.329], depression (β= -0.565; 95% CI [-1.443, -0.071]), systolic blood pressure (β= 1.355; 95% CI [0.298, 2.864]), triglycerides (β=0.365; 95% CI [0.017, 1.087]), HOMA-IR (β= -1.089; 95% CI [-2.121, -0.425]) and hsCRP (β= -2.521; 95% CI [-4.111, -1.265]), contributing to 22.2% of the variances in cognitive function (Full IQ) of these children. This study highlights the importance of psychological factors and cardiovascular disease risk factors as mediators of the relationship between overweight/obesity and cognitive function in children. Consequently, future interventions should not only target the reduction of weight but also target to reduce the cardiovascular disease risk factors through lifestyle modifications and improve psychological health for the prevention of poorer cognitive performance in overweight/obese children.